Computational Analysis of Chromophore Tripeptides FollowingFusion of Enhanced Green Fluorescent Protein and Cell-penetrating Peptides - Widyaningtyas, Silvia Tri; Pratiwi, Ekawati Betty; Bela, Budiman (Makara Journal of Science, 2020)
Cell-penetrating peptides (CPPs) are small peptides that can transfer other materials into a cellular compartment. In this research, we studied the effect of fusion of new CPPs to the N-terminal of enhanced Green Fluorescent Protein eGFP on the ability of the latter to fluoresce. Results showed that the recombinant protein CPPs-eGFP could be successfully expressed in Escherichia coli. In contrast to E. coli expressing wild-type eGFP, which could fluoresce under ultraviolet (UV) or visible light, E. coli expressing CPPs-eGFP lost their ability to fluoresce. PyMol, a molecular visualization system, revealed that fusion of the new CPPs to the N-terminal of eGFP alters interactions between chromophore-forming tripeptides and the adjacent amino acids of other tripeptides. Disrupting peptide interactions induced structural changes in eGFP that caused it to lose its fluorescence ability. We suggest performing computational analyses to predict the biological function of new fusion proteins prior to starting laboratory work.